Makedonska kulturna dediščina kot predmet politične manipulacije skozi prizmo arhitekturno-političnega projekta Skopje 2014 - Filak, Manca (Etnolog. Nova vrsta (Ljubljana), 2018)
The article addresses the capital of Macedonia, Skopje, and the current changes in the town resulting from the Skopje 2014 political architecture project. Because of its grand dimensions and controversial nature, the project has changed the appearance of the town, as well as the attitude of the inhabitants of Skopje and Macedonia to the cultural heritage since the beginning of 2010. The article analyses the development of the town in different historical periods leading to the present condition; the emphasis is on the modernist project following the Skopje earthquake of 1963, and the period of the Skopje 2014 project. Both projects are examples of the attitude of politics and the government to regulating the cultural heritage and, consequently, (re)creating the national identity.
Keywords: cities and towns; cultural heritage; cultural policy; cultural property; kulturna dediščina; kulturna politika; mesta; nacionalizem; nationalism; projects; projekti; Skopje (Macedonia); Skopje (Makedonija)